Influences of human activity and climate change on growing-season soil moisture in the Qinghai–Tibet grasslands from 2000 to 2020 - Xiao, Jianyu; Yu, Chengqun; Fu, Gang (Frontiers in Ecology and Evolution, 2023)
Soil moisture (SM) serves as a vital indicator reflecting environmental water conditions, but significant uncertainties still persist regarding how human activity and climatic change affect SM. In this study, we quantified the influences of human activity and climatic change on growing-season SM in the Qinghai-Tibet grasslands from 2000 to 2020. Climatic change led to a decline in spatially mean SM at a rate of -0.01 and -0.06 g g -1 yr -1 at 0-10 and 10-20 cm, respectively. Nonetheless, climatic change caused the soil to become wetter in 39.97% and 22.29% areas at 0-10 and 10-20 cm, respectively. Human activity resulted in a decline in spatially mean SM by 36% and 21% at 0-10 and 10-20 cm, respectively. Nonetheless, human activity caused soil to become wetter in 2.82% areas at 0-10 cm and 30.03% areas at 10-20 cm. Therefore, both climate change and human activity have contributed to a pattern where the whole Qinghai-Tibet grasslands became drier, while specific parts became wetter during the last 20 years. Besides temperature and precipitation change, we should also pay attention to the response of SM to radiation change.